The country gentleman - Tucker, Luther, 1802-1873; Thomas, John J. (John Jacobs), 1810-1895 (Luther Tucker, 1853)
"A journal for the farm, the garden, and the fireside, devoted to improvement in agriculture, horticulture, and rural taste; to elevation in mental, moral, and social character, and the spread of useful knowledge and current news;" subtitle varies.